Exigência térmica e produtividade da amoreira-preta em função das épocas de poda - Segantini, Daniela Mota [UNESP]; Leonel, Sarita [UNESP]; Cunha, Antonio Ribeiro Da [UNESP]; Ferraz, Rafael Augusto [UNESP]; Ripardo, Ana Karolina Da Silva [UNESP] (Sociedade Brasileira de Fruticultura, 2014)
November and February are the harvest season for blackberry at the southern states of Brazil, where is the largest cultivation area in the country. It is Known that the fruit offered outside the harvest season has higher prices, so the present study aimed to stagger the harvest season for blackberry, by performing the winter pruning at different time, taking into account the number of hours exposed to cold temperatures and accumulated degree-days. This study was conducted at the Fazenda Experimental São Manuel, at São Manuel-SP. It was used blackberry plants cv. Tupy, 3 years old, conducted in 4 main stems in espalier in T, with 1.2 meters high. The experimental design was a 2x5 factorial arrangement, with two cropping systems (irrigated and non-irrigated) and 5 treatments (pruning times: 05/20, 06/26, 07/24, 08/23 and 09/26) with blocks repetitions. Irrigation did not alter the cycle of blackberry, but resulted in higher productivity independent of pruning time. The higher the number of chilling hours accumulated, the lower the cycle and the need for day-degrees of the blackberry 'Tupy'. The winter pruning held on 05/20 provided the highest blackberry harvest in mid-September, at São Manuel - SP.

O período de colheita de amora-preta ocorre de novembro a fevereiro nos estados do Sul do Brasil, onde se concentra a maior área de cultivo do País. Sabendo-se que frutas ofertadas fora do pico da safra possuem preços mais vantajosos, objetivou-se escalonar a colheita da amoreira-preta através da realização da poda hibernal em diferentes épocas, levando-se em conta o número de horas de frio e os grausdia acumulados. O presente trabalho foi conduzido na Fazenda Experimental São Manuel, no município de São Manuel-SP. Foram utilizadas plantas de amoreira-preta Tupy, de 3 anos de idade, conduzidas em 4 hastes principais, em espaldeira em T, com 1,2 metro de altura. O delineamento experimental utilizado foi o esquema fatorial 2x5, constando de 2 sistemas de cultivo (não irrigado e irrigado) e de 5 tratamentos (épocas de poda: 20-05, 26-06, 24-07, 23-08 e 26-09), com repetições em blocos. A irrigação não alterou a duração do ciclo da amoreira-preta, mas proporcionou aumento na produtividade, independentemente das épocas de poda. Quanto maior o número de horas de frio acumulado, menor o ciclo e menor a necessidade em graus-dia da amoreira-preta 'Tupy'. A poda hibernal realizada em 20-05 proporcionou um pico de colheita de amora-preta em meados de setembro, em São Manuel - SP.
Thermal requirement and productivity in blackberry-function times of pruning
Keywords: Rubus sp; produção; graus-dia; ciclo; qualidade; Rubus sp; productivity; day-degrees; cycle; quality